2018
DOI: 10.7812/tpp/18-093
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned from Implementation of the Food Insecurity Screening and Referral Program at Kaiser Permanente Colorado

Abstract: USDA) prohibits discrimination in all of its programs and activities on the basis of race, color, national origin, age, disability, and where applicable, sex (including gender identity and expression), marital status, familial status, parental status, religion, sexual orientation, political beliefs, genetic information, reprisal, or because all or part of an individual's income is derived from any public assistance program. (Not all prohibited bases apply to all programs.) Persons with disabilities who require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 25 publications
(14 reference statements)
1
80
0
Order By: Relevance
“…This structure provides a useful framework through which oncologists also can identify food insecurity. 71 Many food assistance programs have restricted service hours, documentation requirements, and a limited quantity and choice of food. 20 Several resources and interventions currently are available to patients who are food insecure.…”
Section: Proposals For Practicementioning
confidence: 99%
See 1 more Smart Citation
“…This structure provides a useful framework through which oncologists also can identify food insecurity. 71 Many food assistance programs have restricted service hours, documentation requirements, and a limited quantity and choice of food. 20 Several resources and interventions currently are available to patients who are food insecure.…”
Section: Proposals For Practicementioning
confidence: 99%
“…70 Numerous previous studies have shown that patients referred to food resources in response to a positive clinical screen for food insecurity need support (from a case manager, social worker, or navigator) to navigate a complex ecosystem of resources, rather than just being handed a list of community opportunities. 71 Many food assistance programs have restricted service hours, documentation requirements, and a limited quantity and choice of food. 72 However, the sector is evolving rapidly, and many communities have programs optimized for providing access to highly nutritious foods at times and in places that are convenient for the patients using them.…”
Section: Proposals For Practicementioning
confidence: 99%
“…21 Kaiser Permanente Colorado and Hunger Free Colorado, for instance, entered into a partnership in 2011, leveraging their unique assets to screen patients for food insecurity during clinical visits, refer food-insecure patients to community specialists with expertise in community and federal nutrition programs, and support enrollment in appropriate programming. 22 Other clinical systems have adopted on-site solutions. For example, ProMedica health system has screened all patients for food insecurity since 2015.…”
Section: Opportunities/early Successesmentioning
confidence: 99%
“…Consistent with existing literature, participants in our study described how their food budgets were limited after paying for "priority" items such as housing, childcare, and medical bills (17). Healthcare institutions are testing models to employ community navigators or community health workers to connect families to programs for food security and broader services, with promising results (12,40). For example, a healthcare system in Colorado implemented community specialists in an active referral process to connect patients with social assistance, including food programs, increasing the percentage of referred patients using a resource hotline from 5 percent to 75 percent (39).…”
Section: Discussionmentioning
confidence: 52%